2021
DOI: 10.4314/gjg.v13i2.5
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of indigenous knowledge in conserving natural forests in the face of modernisation: The case of Makete District, Southern Highlands of Tanzania

Abstract: In pre-colonial Africa, Indigenous Knowledge (IK) was very effective in conserving natural forests because it was free from the current challenges. Therefore, this paper assesses effectiveness and sustainability of IK in conserving natural forests. It also examines the impact of modernisation on IK. The study employed mixed research methods to triangulate information. Thus, the data were collected through in-depth interview, Focus Group Discussions (FGDs), field observation and household survey. The study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The study area was selected because Makete district is one of the districts in Southern Highlands with high rate of natural forests loss (URT, 2011). Additionally, the district was chosen for the study because it has many forests conserved traditionally compared to other districts in the Southern Highlands of Tanzania, which have highly occupied by plantation forests (Sanga, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area was selected because Makete district is one of the districts in Southern Highlands with high rate of natural forests loss (URT, 2011). Additionally, the district was chosen for the study because it has many forests conserved traditionally compared to other districts in the Southern Highlands of Tanzania, which have highly occupied by plantation forests (Sanga, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, nowadays, legends lost their power due to the influence of modernization. Sanga (2021) found that modernization caused people to lose trust on what was conducted by elders. It also caused people, especially youth, to perceive traditional beliefs and practices as outdated and old fashioned.…”
Section: Indigenous Cultural Practices Employed To Conserve the Natur...mentioning
confidence: 99%